Clinical Profile of Patients with Hemifacial Spasm at a Tertiary Eye Care Center in South India: A Retrospective Study - Manisha Kalher; Madhurima Kaushik; Haritha Vasudevan; Siddharth Narendran; Karthik Kumar Mani; Kavitha Ramakrishnan; Viji Rangarajan; Virna Mahesh Shah (Journal of Current Ophthalmology)
Purpose: To assess the incidence and clinical profile of hemifacial spasm (HFS) and the association between HFS and systemic diseases. Methods: This retrospective study was carried out on 85 patients with HFS, presenting at a tertiary eye care center in South India. Demographic and clinical details were recorded for all patients. Of these, the patients who had undergone magnetic resonance imaging (MRI) of the brain were analyzed for primary and secondary HFS. Results: The mean age of the patients was 56.11 ± 12.51 years. The age at onset of HFS was 54.9 ± 12.7 years. The disease duration was 9.51 ± 7.28 years. Male:female ratio was 1:1.17. The right side was involved in 31 patients (36.47%) and the left side in 54 patients (63.52%). MRI was performed in 54 (63.52%) patients and showed neurovascular conflict in 22 (40.74%) patients and space-occupying lesions in 2 (3.70%) patients. Forty-nine (57.64%) patients had primary HFS, while five (5.88%) patients had secondary HFS due to old facial palsy in 3 and space-occupying lesions in two patients. Twenty (23.52%) patients received botulinum toxin A with a good response. Type of HFS had a significant association with hypertension (P = 0.046) while no significant association was present between laterality of HFS and systemic diseases (P > 0.05 each). Multivariate analysis showed a marginally significant association between type of HFS and hypertension (P = 0.057). Conclusions: Primary HFS was the main type of HFS with female dominance and predilection for the left side. Hypertension had a relationship with HFS that needs to be investigated further for its causal nature.